Large deviations and metastability - Olivieri, Enzo, 1945- (Encyclopedia of mathematics and its applications, 2005)
The book provides a general introduction to the theory of large deviations and a wide overview of the metastable behaviour of stochastic dynamics. Written to be accessible to graduate students, this book provides an excellent route into contemporary research.